Does Practice Enhance Adaptability? The Role of Personality Trait, Supervisor Behavior, and Career Development Training - Mei, Mei; Yang, Fu; Tang, Mingfeng (Frontiers in Psychology, 2021)
Drawing upon career construction theory, we examined the mediating effect of deliberate practice on career adaptability and the effects of learning goal orientation and supervisor incompetence accusation as well as career development training on deliberate practice. Using data collected from 204 Chinese PhD students in three waves over a period of two months, we found that individuals who were inclined to learn new skills and obtain new knowledge were more likely to deliberately practice professional activities in their fields. When a PhD student's professional competence was questioned by his or her supervisor, the student was more prone to negative emotions and would reduce his or her effort in the development of expertise. Career development training—contrary to expectations—negatively predicted deliberate practice of professional activities. One possible reason is that the participants in this study have strong autonomy so that those who really struggling are participating in training and seeking help and those who with strong professional abilities are not accessing training programs. Moreover, results showed that deliberate practice of professional activities significantly promoted PhD students to adapt to their academic circumstances. Implications for career-related practice within the academic domain are provided.